2011
DOI: 10.1176/appi.ajp.2010.09121816
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Follow-Up of Bipolar Disorder in Women With Premenstrual Exacerbation: Findings From STEP-BD

Abstract: Women with bipolar disorder and premenstrual exacerbation have a worse course of illness, a shorter time to relapse, and greater symptom severity, but they are not more likely to meet criteria for rapid cycling. Premenstrual exacerbation may be a clinical marker predicting a more symptomatic and relapse-prone phenotype in reproductive-age women with bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 38 publications
(55 reference statements)
4
30
0
Order By: Relevance
“…In BD I, only a nonsignificant trend was observed. Sixty to seventy percent of women with BD have been reported to experience premenstrual exacerbation of their symptoms, and about 27% of women with BD have a lifetime diagnosis of PMDD according to the DSM-IV criteria (Dias et al, 2011;Payne et al, 2007). Regarding the bipolar subtype, PMDD was more common in BD II .…”
Section: Discussionmentioning
confidence: 99%
“…In BD I, only a nonsignificant trend was observed. Sixty to seventy percent of women with BD have been reported to experience premenstrual exacerbation of their symptoms, and about 27% of women with BD have a lifetime diagnosis of PMDD according to the DSM-IV criteria (Dias et al, 2011;Payne et al, 2007). Regarding the bipolar subtype, PMDD was more common in BD II .…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports and prospective studies suggest that women who experience premenstrual symptom exacerbation are more likely to have a highly symptomatic and relapse prone illness 544, 545. One of the largest studies (n = 1099) found that women who met DSM‐5 provisional criteria for premenstrual dysphoric disorder (PMDD) had an earlier illness onset, more comorbid Axis I disorders, a higher number of hypomanic/manic and depressive episodes, and higher rates of rapid cycling 546.…”
Section: Specific Populationsmentioning
confidence: 99%
“…In the longitudinal STEP-BD study, among women with BD (n = 293), those with premenstrual exacerbation had more episodes (primarily depressive), more depressive and manic symptoms overall, a shorter time to relapse, and greater symptom severity (186). Premenstrual exacerbation may predict a more symptomatic and relapse-prone phenotype in women with BD.…”
Section: Premenstrual Syndrome (Pms) ⁄ Premenstrual Dysphoric Disordementioning
confidence: 99%